Animals that are Good to Live With: Theoretical Reflections on Kinship Relations with Pets - Nevena Milanović Minić (Etnoantropološki Problemi)
The paper explores the phenomenon of keeping pets as family members from an anthropological perspective. It traces the historical and cultural transformation of dogs and cats from utilitarian working animals to emotional companions and kin. Drawing on anthropological literature, the paper highlights how human–animal relationships are socially constructed and culturally variable. Pets are no longer perceived solely as property or function-bearing beings, but as sentient subjects involved in household dynamics. Through concepts such as anthropomorphism, sentimental projection, and emotional reciprocity, the paper analyzes how animals are integrated into kinship systems. The notion of "companion species" (Haraway) is used to argue for an ethics of mutuality, responsibility, and care. This paper critically engages with Baudrillard’s idea of “sentimental racism,” suggesting that empathy toward animals is not always a form of domination or projection. Instead, relationships with pets often reveal deep emotional and social bonds that reshape our understanding of family and domestic life. Ethnographic and theoretical insights show that pets are active participants in social life, not passive symbols. By analyzing pets as kin, the study contributes to multispecies anthropology and challenges anthropocentric notions of belonging. Ultimately, it calls for a reconsideration of the moral and political status of animals in human communities.